Simplifying
16y^{2} + -1 = 0
Reorder the terms:
-1 + 16y^{2} = 0
Solving
-1 + 16y^{2} = 0
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + 16y^{2} = 0 + 1
Combine like terms: -1 + 1 = 0
0 + 16y^{2} = 0 + 1
16y^{2} = 0 + 1
Combine like terms: 0 + 1 = 1
16y^{2} = 1
Divide each side by '16'.
y^{2} = 0.0625
Simplifying
y^{2} = 0.0625
Reorder the terms:
-0.0625 + y^{2} = 0.0625 + -0.0625
Combine like terms: 0.0625 + -0.0625 = 0.0000
-0.0625 + y^{2} = 0.0000
Factor a difference between two squares.
(0.25 + y)(-0.25 + y) = 0.0000
#### Subproblem 1

Set the factor '(0.25 + y)' equal to zero and attempt to solve:
Simplifying
0.25 + y = 0
Solving
0.25 + y = 0
Move all terms containing y to the left, all other terms to the right.
Add '-0.25' to each side of the equation.
0.25 + -0.25 + y = 0 + -0.25
Combine like terms: 0.25 + -0.25 = 0.00
0.00 + y = 0 + -0.25
y = 0 + -0.25
Combine like terms: 0 + -0.25 = -0.25
y = -0.25
Simplifying
y = -0.25
#### Subproblem 2

Set the factor '(-0.25 + y)' equal to zero and attempt to solve:
Simplifying
-0.25 + y = 0
Solving
-0.25 + y = 0
Move all terms containing y to the left, all other terms to the right.
Add '0.25' to each side of the equation.
-0.25 + 0.25 + y = 0 + 0.25
Combine like terms: -0.25 + 0.25 = 0.00
0.00 + y = 0 + 0.25
y = 0 + 0.25
Combine like terms: 0 + 0.25 = 0.25
y = 0.25
Simplifying
y = 0.25#### Solution

y = {-0.25, 0.25}